Mechanized Rice Cultivation Through Smart Farming Using Artificial Intelligence Basis of Rice Farmers in Bongabong, Oriental Mindoro - Saguid John Rex; Valdez Kaycee; Magbanua Jonnel; Villaluna Vinz Philip; Nicko A. Magnaye; Jesselle P. Atienza (International Journal of Integrative Research, 2023)
Mechanized rice cultivation through smart farming using artificial intelligence (AI) has gained considerable interest as a means to improve agricultural practices and increase productivity. This study focuses on the application of smart farming technology in Bongabong, Oriental Mindoro, Philippines, with the aim of optimizing rice production. Data were collected through self-administered questionnaires, and statistical analyses using descriptive and inferential statistics were conducted. The findings indicate a gender imbalance among farmers utilizing smart farming technologies, with a higher representation of males. The study identified challenges in terms of limited trained operators, inadequate infrastructure and support facilities, high operational costs, and market limitations. The study also highlighted the environmental implications of smart farming technology, such as improved water management, reduced chemical inputs, and enhanced soil health. Overall, the study underscores the importance of education, training, and collaborative efforts to promote the adoption of smart farming technology in rice cultivation. By leveraging AI and innovative farming techniques, rice farmers in Bongabong, Oriental Mindoro can enhance productivity, sustainability, and economic outcomes.